IMPLEMENTASI PERATURAN MENTERI SOSIAL RI NOMOR 10 TAHUN 2017 TENTANG PROGRAM KELUARGA HARAPAN DI KELURAHAN SEMPAJA UTARA KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Henny Vera Waty; Achmad Djumlani; Abdullah Karim (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
The purpose of this study is to describe and analyze the implementation of the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 10 of 2017 concerning the Family Hope Program in Sempaja Utara Village, North Samarinda District, Samarinda City along with the factors that hinder the implementation of this policy. This research is a qualitative type, with research locations in the area of North Sempaja Village and Samarinda City Social Service and East Kalimantan Provincial Social Service. Drawing conclusions based on data processed using interactive model analysis. The results of this study explain that the implementation of the Regulation of the Minister of Social Affairs Number 10 of 2017 concerning the Family Hope Program in Sempaja Utara Village, North Samarinda District, Samarinda City has generally been going well and smoothly. Conclusion The role of the local government in terms of implementing the Regulation of the Minister of Social Affairs Number 10 of 2017 concerning the Family Hope Program in the North Sempaja Exit, North Samarinda District, Samarinda City is highly expected, especially for access to public transportation at the location of aid recipients and the need to recruit additional PKH assistants so that they do not there is an overload of client assistance that exceeds the maximum standard of mentors, as well as adding operational facilities and funds for PKH facilitators so that implementation in the field will be carried out more smoothly, quickly and effectively.Keywords: Implementation, Family Hope Program, North Sempaja Village